The Effect of STEM Integration on Scientific Literacy and Scientific Attitudes: An Empirical Study in Primary Education - Sales, Reka Monika; Bentri, Alwen; Fitria, Yanti; Hidayati, Abna (Jurnal Paedagogy, 2026)
This study aims to examine the effect of implementing the Science, Technology, Engineering, and Mathematics (STEM) approach on elementary school students’ scientific literacy and scientific attitudes. A quasi-experimental method with a one-group pretest–posttest design was employed. The participants consisted of 30 third-grade students from SD Negeri 100206 Pintu Padang, South Angkola District. Data were collected using a scientific literacy test in the form of essay questions, a scientific attitude questionnaire, and observation sheets to assess the implementation of the learning process. The data were analyzed quantitatively using the normalized gain (N-gain) to measure the level of improvement and a paired-sample t-test to determine the significance of differences between pretest and posttest scores. Prior to hypothesis testing, prerequisite tests, including tests of normality and homogeneity, were conducted. The findings indicate that the implementation of the STEM approach led to a substantial improvement in students’ scientific literacy. The mean score increased from 48.33 in the pretest to 88.33 in the posttest, with an N-gain value of 0.77, categorized as high. Similarly, students’ scientific attitudes improved significantly, with the mean score increasing from 49.50 to 89.17 and an N-gain value of 0.78, also classified as high. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05), indicating statistically significant differences between pretest and posttest scores. These results suggest that the STEM approach is effective in enhancing both cognitive aspects (scientific literacy) and affective aspects (scientific attitudes). This effectiveness may be attributed to the characteristics of third-grade students, who are in the concrete operational stage of cognitive development. At this stage, students learn more effectively through direct experiences, hands-on activities, and real-life problem-solving. The STEM approach accommodates these needs by engaging students in practical investigations, collaborative tasks, and contextual learning, thereby making abstract concepts more tangible and meaningful. Therefore, the integration of STEM in science learning can be considered an effective instructional strategy to enhance students’ engagement, critical thinking, and problem-solving skills in elementary education.